Análise integrada do tratamento de esgotos domésticos e da qualidade das águas superficiais nas bacias hidrográficas do Rio das Velhas e dos Rios Jequitaí e Pacuí - MG - Marina Salim Dantas (2020)
Rapid growth of Brazilian population in recent decades, especially in large urban centers, has led to greater demand for water resources, with consequent increase in generation of domestic and industrial effluents. In the country, 45% of the urban population is not supplied by wastewater treatment. Even when treatment is carried out, many municipalities do not have adequate levels of contaminant removal. Thus, wastewater disposal into receiving bodies puts pressure on water resources, affecting downstream uses. For wastewater treatment plants (WWTPs) in operation, it is necessary to monitor operational conditions of the system in order to improve its performance and meet regulatory standards. The objective of this research is to assess, in an integrated manner, the treatment of domestic effluents and the surface water quality in the Velhas River basin and the Jequitaí and Pacuí Rivers basin. Monitoring data from raw and treated sewage as well as from receiving water bodies were obtained. Monitoring data from the Minas Gerais Institute of Water Management were also obtained. The results of each WWTP were compared with typical ranges reported in literature for raw and treated wastewater, and removal efficiencies. Considering the data on the effluent concentrations and the removal efficiencies of each parameter, statistical tests were applied to compare the operational performances among the WWTPs located in each basin. Regarding the monitoring data of the receiving water bodies, a statistical test was applied to compare the data gathered upstream and downstream of each disposal. In the Jequitaí and Pacuí Rivers basin, more concentrated raw effluent than what is usually reported was found, and in both basins significant differences were identified in the operational performance of the treatment plants. In the Velhas River basin, different performances were found for plants of the same treatment type, which demonstrates the importance of proper management and operation. Significant alterations in the receiving bodies of both basins resulting from the discharge of the treated effluents were found. From the IGAM monitoring data, it was possible to identify the spatial variability in water quality of the two basins. The situation experienced by full-scale treatment systems during the study period was determined, highlighting the weaknesses in the monitoring databases. Some features of the basins that lead to greater pressure on water bodies are the high degree of urbanization and high population density in the Velhas River basin and the lower water availability, with watercourses with reduced dilution capacity in the Jequitaí and Pacuí Rivers basin.